2017
DOI: 10.1002/cplu.201600646
|View full text |Cite
|
Sign up to set email alerts
|

Planar Anthracene–Acetylene Frameworks as a Stereogenic Motif

Abstract: Planar and rigid frameworks that consist of two 1,8‐substituted anthracene units and two acetylene linkers were utilized as key structures for the generation of stereoisomers through the introduction of extra substituents. These compounds were synthesized from 1,8‐substituted anthracene building units by a combination of coupling reactions. We designed diastereomers, enantiomers, and topomers by modifying the combination of the two linkers and the number of substituents at sterically crowded intraannular posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…For calculations of molecules involving π‐electron interactions, the choice of the calculation level is essential. Systematic theoretical studies by Truhlar's group as well as our previous studies on the calculations of anthracene macrocyclic compounds and the gear system of 6 [5d] suggested that some Minnesota family functionals reasonably reproduced the experimental data by considering the π ··· π and related interactions suitably within acceptable computational times. In contrast, the B3LYP functional, one of the most common functionals, considerably underestimated such interactions without dispersion terms.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For calculations of molecules involving π‐electron interactions, the choice of the calculation level is essential. Systematic theoretical studies by Truhlar's group as well as our previous studies on the calculations of anthracene macrocyclic compounds and the gear system of 6 [5d] suggested that some Minnesota family functionals reasonably reproduced the experimental data by considering the π ··· π and related interactions suitably within acceptable computational times. In contrast, the B3LYP functional, one of the most common functionals, considerably underestimated such interactions without dispersion terms.…”
Section: Resultsmentioning
confidence: 96%
“…To evaluate the overall interactions between the Tp units in the macrocyclic compounds, we calculated thermochemical data by using homodesmotic (HD) reactions , . We designed the HD reactions shown in Scheme , for which the reactants were a macrocyclic compound (or its model) and ethyne ( 20 ), and the products were 9,10‐diethynyl‐Tp and 1,2‐diethynylbenzene ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…The selected examples of strained macrocycles are depicted in Figure . Fan‐blade‐shaped macrocycle 187 was synthesized as a racemic mixture by Eglinton coupling . The pure enantiomer could be resolved by using chiral high‐performance liquid chromatography.…”
Section: Angle‐strained Alkyne‐containing π‐Conjugated Macrocyclesmentioning
confidence: 99%
“…Fan-blade-shaped macrocycle 187 was synthesized as ar acemic mixture by Eglinton coupling. [305][306][307][308] The pure enantiomer could be resolved by using chiral high-performance liquid chromatography. DFT calculations pointed out that the macrocyclic structure is slightly distorted because of the stericr epulsion between ah ydrogen atom and am ethoxy group inside the macrocyclic ring.…”
Section: Thiophene Spacersmentioning
confidence: 99%
“…16 So far, tethered anthracene dimers reported in the literature contain diverse linker groups, ranging from p-conjugated bridges (e.g., phenylenes, phenylacetylenes, oligoynes) to non-conjugated ethers, urea, ester, and sulfur groups. Depending on the shape and number of linker groups, the structures of tethered anthracene dimers can be divided into three types, namely linear, 17,18 bent, [19][20][21] and macrocyclic [22][23][24][25] (see Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%